Makna Rumah Tinggal (Laika Landa) bagi Masyarakat Tolaki di Desa Sandarsi Jaya Kecamatan Angata - Harnita .; Wa Ode Sitti Hafsah (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2017)
This study aims to find and describe the house (laika landa) in Tolaki tribe community in Sandarsi Jaya Village and to know and describe meaning of the house (laika landa) for Tolaki tribe community in Sandarsi Jaya Village. This research was conducted in Sandarsi Jaya Village, District of Angata, South Konawe Regency. Data collection have done through observation (observation), indepth interview and documentation. The data obtained analyzed descriptively qualitative. The results of this study indicate that laika landa is a form of architecture in Tolaki tribe community in Sandarsi Jaya Village which is established on the pole and it is a temporary residence for people who work as farmers in fields. Besides, there are also houses that are established like laika landa, but the function is different with laika landa. it is functioned as residence settled for the community in Sandarsi Jaya Village which is also in the middle of the village. Keywords: meaning, laika landa, Tolaki tribe community